Adhesive Capsulitis in the Elderly with Diabetes Mellitus and Hypertension: A Reflection of Multimorbidity and the Importance of Family-Centered Care - Dasa Novita, Khuznita; Nur Cahyani, Aulia; Rico Abdul Karim, Muhammad (Jurnal Ilmu Kedokteran Keluarga, 2026)
Adhesive capsulitis is a common musculoskeletal disorder in older adults and is often associated withchronic diseases such as diabetes mellitus (DM) and hypertension (HT). A 76-year-old womanpresented with shoulder pain and restricted motion. She had type 2 DM with neuropathy and long-standing HT, with a family history of cardiovascular disease. Examination showed marked limitationof active and passive shoulder movement, consistent with the frozen stage of adhesive capsulitis. Thepatient received NSAIDs and physiotherapy, along with caregiver education on exercises, routinefamily screening for DM and HT, and reinforcement of self-care. Community interventions includedgroup exercise promotion, free health screenings, and counseling on chronic disease management.This case highlights the value of comprehensive management for adhesive capsulitis in elderlypatients, emphasizing family- and community-based interventions to improve adherence, preventcomplications, and maintain quality of life.